2022
DOI: 10.1038/s41746-022-00591-z
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variation in objective measure of reactogenicity following COVID-19 vaccination via smartwatches and fitness bands

Abstract: The ability to identify who does or does not experience the intended immune response following vaccination could be of great value in not only managing the global trajectory of COVID-19 but also helping guide future vaccine development. Vaccine reactogenicity can potentially lead to detectable physiologic changes, thus we postulated that we could detect an individual’s initial physiologic response to a vaccine by tracking changes relative to their pre-vaccine baseline using consumer wearable devices. We explor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…While our cohort size is relatively reasonable compared to other studies using wearable devices, it has a rather large paired-wise sample 18,19,21 . In particular, most of the participants in our second booster analysis are over 50 years old, in line with current Israeli and CDC vaccine administration guidelines 22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While our cohort size is relatively reasonable compared to other studies using wearable devices, it has a rather large paired-wise sample 18,19,21 . In particular, most of the participants in our second booster analysis are over 50 years old, in line with current Israeli and CDC vaccine administration guidelines 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated the excellent performance of wearable sensors such as smartwatches in detecting physiological changes following vaccination, as they can continuously monitor reactions in an objective manner 1821 . Impressively, they have been shown to be even more sensitive than humans in detecting vaccine reactions 18,19 , even in individuals who did not report any reactions following vaccination 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shabbir and collaborators (28) have implemented a strategy based on exploratory data analytics from diverse sources, coupled with telemonitoring and the use of internet of things (29)(30)(31) to detect COVID-19 severity in the context of smart hospitals (32)(33)(34). Also relevant is the use of concepts from computational social science (ambient intelligence, in particular) and again data from wearables (in this case, smartwatches) to develop early warning alerts (35)(36)(37). Several additional approaches to use machine learning to prevent or warn in advance for COVID-19 are discussed in the monographic review by Saeed et al (38).…”
Section: Introductionmentioning
confidence: 99%
“…The level of deviation from normal was moderate. For example, a mean increase of only 1.5 beats per minute in resting heart rate, a decrease of 1,600 daily step count and an increase of 35 min of night sleep were observed after a second mRNA vaccine dose 7 . Yet these findings tracked well with established knowledge of subjective assessments of reactogenicity, such as significantly greater changes in those receiving the Moderna versus the Pfizer/BioNTech vaccine and in those receiving the first dose response in people with prior COVID-19 infection (Fig.…”
mentioning
confidence: 98%